PATRIARCHAL RECONSTRUCTION IN PEREMPUAN KEUMALA BY ENDANG MOERDOPO: A STUDY OF HORNEY’S THEORY OF PSYCHO-FEMINISM - Nugroho, Bayu Aji; Sudirman, Eka Pratiwi; M, Fatimah; Max, Jonathan Irene Sartika Dewi (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study formulated the following problems: (1). How is the depiction of patriarchy in “Perempuan Keumala” novel by Endang Moerdopo? (2). How is the form of patriarchal reconstruction in in the novel according to Karen Horney’s theory of psycho feminism? Those research problems aim to find out the correlation between patriarchal forms of culture experienced by women and the patriarchal forms that appear in the novel. This study uses Qualitative Descriptive analysis method. It is a method in which researchers attempt to describe what they have read according to the primary and secondary data sources. The researchers use Karen Horney’s theory of psycho feminism which stated that women’s resistance is generated from their parenting style and social environment.  Women’s resistance is psychoanalytically divided into three forms: moving towards people, against people, and moving away from people. Those movements cause women to have several self-defense mechanisms: displacement, sublimation, identification, and repression.